Stem Cell Metabolism in Cancer and Healthy Tissues: Pyruvate in the Limelight - Corbet, Cyril (Frontiers in Pharmacology, 2018)
Normal and cancer stem cells share the remarkable potential to self-renew and differentiate into many distinct cell types. Although most of the stem cells remain under quiescence to maintain their undifferentiated state, they can also undergo cell divisions as required to regulate tissue homeostasis. There is now a growing evidence that cell fate determination from stem cells implies a fine-tuned regulation of their energy balance and metabolic status. Stem cells can shift their metabolic substrate utilization, between glycolysis and mitochondrial oxidative metabolism, during specification and/or differentiation, as well as in order to adapt their microenvironmental niche. Pyruvate appears as a key metabolite since it is at the crossroads of cytoplasmic glycolysis and mitochondrial oxidative phosphorylation. This Review describes how metabolic reprogramming, focusing on pyruvate utilization, drives the fate of normal and cancer stem cells by modulating their capacity for self-renewal, clonal expansion/differentiation, as well as metastatic potential and treatment resistance in cancer. This Review also explores potential therapeutic strategies to restore or manipulate stem cell function through the use of small molecules targeting the pyruvate metabolism.